Interventional NIR Fluorescence Imaging of Cancer: Review on Next Generation of Dye-Loaded Protein-Based Nanoparticles for Real-Time Feedback During Cancer Surgery - Borlan R (Dove Medical Press, 2021)
Raluca Borlan,1,2 Monica Focsan,2 Dana Maniu,1 Simion Astilean1,2 1Biomolecular Physics Department, Faculty of Physics, Babeș-Bolyai University, Cluj-Napoca, Cluj, Romania; 2Nanobiophotonics and Laser Microspectroscopy Centre, Interdisciplinary Research Institute in Bio-Nano-Sciences, Babeș-Bolyai University, Cluj-Napoca, Cluj, RomaniaCorrespondence: Simion Astilean Email simion.astilean@ubbcluj.roMonica Focsan Email monica.iosin@ubbcluj.roAbstract: The use of fluorescence imaging technique for visualization, resection and treatment of cancerous tissue, attained plenty of interest once the promise of whole body and deep tissue near-infrared (NIR) imaging emerged. Why is NIR so desired? Contrast agents with optical properties in the NIR spectral range offer an upgrade for the diagnosis and treatment of cancer, by dint of the deep tissue penetration of light in the NIR region of the electromagnetic spectrum, also known as the optical window in biological tissue. Thus, the development of a new generation of NIR emitting and absorbing contrast agents able to overcome the shortcomings of the basic free dye administration is absolutely essential. Several examples of nanoparticles (NPs) have been successfully implemented as carriers for NIR dye molecules to the tumour site owing to their prolonged blood circulation time and enhanced accumulation within the tumour, as well as their increased fluorescence signal relative to free fluorophore emission and active targeting of cancerous cells. Due to their versatile structure, good biocompatibility and capability to efficiently load dyes and bioconjugate with diverse cancer-targeting ligands, the research area of developing protein-based NPs encapsulated or conjugated with NIR dyes is highly promising but still in its infancy. The current review aims to provide an up-to-date overview on the biocompatibility, specific targeting and versatility offered by protein-based NPs loaded with different classes of NIR dyes as next-generation fluorescent agents. Moreover, this study brings to light the newest and most relevant advances involving the state-of-the-art NIR fluorescent agents for the real-time interventional NIR fluorescence imaging of cancer in clinical trials.Keywords: clinical translation, fluorescent contrast agents, organic nanoparticles, near-infrared dyes